Very-low-strength evidence suggests that combining ezetimibe or fibrate with statins is no more effective than high-dose statin monotherapy for reducing all-cause mortality. Issue 2 (1st May 2010) - Tenenbaum, Alexander; Fisman, Enrique Z
Abstract : Commentary on: Sharma M Ansari MT Abou-Setta AM . Systematic review: comparative effectiveness and harms of combination therapy and monotherapy for dyslipidemia . Ann Intern Med 2009 ;151 :622 –30 .